Game Character Design as a Mirror of Student Perceptions: A Creative Method for Reflection and Assessment in Educational Settings (Constructionism Conference Proceedings, 2025)
Exploring the potential of game character design as a constructionist, reflective method and evaluative tool in educational settings, this study investigates how students create characters based on the game “Fall of Porcupine” in school-based participatory design workshops. A thematic analysis of character descriptions provides insights into students’ views on the healthcare system, social inequalities, and working conditions. The findings suggest that character creation serves as a medium for students to engage with complex topics, express personal viewpoints, and develop critical perspectives. This approach contributes to innovative assessment methods in constructionist learning environments by making students’ viewpoints, reflection and knowledge visible to teachers and/or researchers.